Quantitation of SARS-CoV-2 neutralizing antibodies with a virus-free, authentic test. Issue 2 (14th April 2022) - Roessler, Johannes; Pich, Dagmar; Albanese, Manuel; Wratil, Paul R; Krähling, Verena; Hellmuth, Johannes C; Scherer, Clemens; von Bergwelt-Baildon, Michael; Becker, Stephan; Keppler, Oliver T; Brisson, Alain; Zeidler, Reinhard; et al.
Abstract: Neutralizing antibodies (NAbs), and their concentration in sera of convalescents and vaccinees are a correlate of protection from COVID-19. The antibody concentrations in clinical samples that neutralize SARS-CoV-2 are difficult and very cumbersome to assess with conventional virus neutralization tests (cVNTs), which require work with the infectious virus and biosafety level 3 containment precautions. Alternative virus neutralization tests (VNTs) currently in use are mostly surrogate tests based on direct or competitive enzyme immunoassays or use viral vectors with the spike protein as the single structural component of SARS-CoV-2. To overcome these obstacles, we developed a virus-free, safe and very fast (4.5 h) in vitro diagnostic test based on engineered yet authentic SARS-CoV-2 virus-like particles (VLPs). They share all features of the original SARS-CoV-2 but lack the viral RNA genome, and thus are noninfectious. NAbs induced by infection or vaccination, but also potentially neutralizing monoclonal antibodies can be reliably quantified and assessed with ease and within hours with our test, because they interfere and block the ACE2-mediated uptake of VLPs by recipient cells. Results from the VLP neutralization test (VLPNT) showed excellent specificity and sensitivity and correlated very well with a cVNT using fully infectious SARS-CoV-2. The results also demonstrated the reduced neutralizing capacity of COVID-19 vaccinee sera against variants of concern of SARS-CoV-2 including omicron B.1.1.529, BA.1.